Creating Markets in the Kyrgyz Republic : Unleashing the Private Sector to Rebuild Development Success - Country Private Sector Diagnostic - International Finance Corporation (Washington, DC: World Bank, 2022)
This country private sector diagnostic (CPSD) for the Kyrgyz Republic assesses the barriers and opportunities for a more forceful development of the private sector in the country. Between 2000 and 2019, gross domestic product (GDP) growth rate averaged 4.4 percent, enabling the Kyrgyz Republic’s ascension to lower-middle-income country status by 2014. Economic growth has been unstable as its sources lacked diversity and were vulnerable to external shocks. Economic growth has been unstable as its sources lacked diversity and were vulnerable to external shocks. If the Kyrgyz Republic wants to inaugurate a new era of faster, more sustainable economic growth, it must more aggressively develop its private sector to support economic diversification and improve productivity.